DAMPAK PERMASALAHAN GLOBAL REFUGEE DI PROVINSI KEPULAUAN RIAU - Akbar, Dhani; Setiawan, Azhari; Putra, Ardi; Triyana, Nadya (JURNAL TRIAS POLITIKA, 2024)
Abstract: Indonesia is eager to cooperate, in this case with the United Nations High Commissioner for Refugees (UNHCR), the International Organization for Migration (IOM) and the International Committee of the Red Cross (ICRC), to achieve world peace and improve the welfare of the world's people. This research aims to examine the problems faced by the Indonesian government, especially in border areas. Concept of securitization which divided several focuses to a case study in the Riau Archipelago Province where there are approximately 500 refugees on Bintan Island and 1,000 in Batam City under the supervision of IOM and UNHCR. The refugee situation in the Riau Islands is a complex and serious problem. Our research reveals the perceptions of local communities as part of civil society who feel the impact and attitudes towards regulations that are still felt to be lame and ineffective in dealing with this problem. Academic contribution of this research is to solve the issue of border area in the perspective of non-traditional security. Abstrak: Indonesia berkeinginan untuk melakukan kerjasama, dalam hal ini dengan United Nations High Commissioner for Refugees (UNHCR), International Organization of Migration (IOM) dan International Committee of Red Cross (ICRC), untuk mencapai perdamaian dunia dan meningkatkan kesejahteraan dari masyarakat dunia. Penelitian ini bertujuan untuk mengkaji permasalahan yang dihadapi oleh pemerintah Indonesia khususnya di wilayah perbatasan. Konsep yang digunakan dalam penelitian ini adalah pendekatan sekuritisasi yang dipecah pada beberapa fokus pada studi kasus di Provinsi Kepulauan Riau yang kurang lebih ada 500 pengungsi di Pulau Bintan dan 1.000 di Kota Batam di bawah pengawasan IOM dan UNHCR. Situasi pengungsi di Kepulauan Riau terbuka sebagai masalah yang kompleks dan serius. Penelitian kami mengungkap persepsi masyarakat lokal sebagai bagian dari civil society merasakan dampak dan sikap terhadap regulasi yang masih dirasa timpang dan kurang efektif dalam menangani problematika ini. Kontribusi akademik yang diperlukan setelah penelitian ini adalah pemecahan masalah dalam sudut pandang keamanan non-tradisional di wilayah perbatasan.